2016
DOI: 10.1002/ange.201601035
|View full text |Cite
|
Sign up to set email alerts
|

CuI/Oxalamide Catalyzed Couplings of (Hetero)aryl Chlorides and Phenols for Diaryl Ether Formation

Abstract: Couplings between (hetero)aryl chlorides and phenols can be effectively promoted by CuI in combination with an N‐aryl‐N′‐alkyl‐substituted oxalamide ligand to proceed smoothly at 120 °C. For this process, N‐aryl‐N′‐alkyl‐substituted oxalamides are more effective ligands than bis(N‐aryl)‐substituted oxalamides. A wide range of electron‐rich and electron‐poor aryl and heteroaryl chlorides gave the corresponding coupling products in good yields. Satisfactory conversions were achieved with electron‐rich phenols as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…To initiate our studies, 4‐bromoanisole ( 1a ) and indole ( 2b ) were selected as model substrates, and 2 mol% Cu 2 O and ligands were used to explore the optimized conditions. As shown in Table , we initially tried PMPBO ( L1 ) as the ligand, which has shown excellent ability in our previous studies on coupling with phenols . The desired product could be obtained when the coupling was carried out in DMSO at 120 °C, but yield was only 30% because of poor conversion (entry 1).…”
Section: Cu2o‐catalyzed Coupling Of 4‐bromoanisole With Indole Under mentioning
confidence: 99%
“…To initiate our studies, 4‐bromoanisole ( 1a ) and indole ( 2b ) were selected as model substrates, and 2 mol% Cu 2 O and ligands were used to explore the optimized conditions. As shown in Table , we initially tried PMPBO ( L1 ) as the ligand, which has shown excellent ability in our previous studies on coupling with phenols . The desired product could be obtained when the coupling was carried out in DMSO at 120 °C, but yield was only 30% because of poor conversion (entry 1).…”
Section: Cu2o‐catalyzed Coupling Of 4‐bromoanisole With Indole Under mentioning
confidence: 99%
“…As expected, the less polar toluene dramatically lowered the reaction yield, probably because of limited K 3 PO 4 solubility (entry 6) . According to the literatures,,, more polar NMP and DMAc were used but the yields were lower than half of that in DMF (entries 7 & 8 vs. entry 1), while the result in DMSO was comparable to that in DMF (entry 9). As a result, it was shown that the solvent effect was significant and more polar solvents were preferable.…”
Section: Resultsmentioning
confidence: 52%
“…Sincere efforts have been made to develop milder reaction conditions and broadening the substrate scope. , However, activation of aryl chlorides has continued to remain a big challenge, until the introduction of oxalic diamides. ,, Recently, Ma and co-workers discovered efficient oxalamide ligands (Figure ) that allow aryl chlorides to be used as the substrate in milder conditions. N , N ′-Bis­(2,4,6-trimethoxyphenyl)­oxalamide (BTMPO) analogues were reported to be very efficient ligands in C–N coupling reactions. , Additionally, Lee’s group reported the first copper-catalyzed coupling of thiols with inactivated aryl chlorides by using oxalic diamides as the ligands .…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the coordination between the ligand and copper­(I) and structure–activity relationship between the ligand and an active copper catalytic species will be a great advantage to predict the performance of the ligands. Several reports on the importance of the CuI/oxalamide system in coupling reactions have been published. ,, There is an extensive scope for the investigation of the mechanism of CuI/oxalamide-promoted reactions.…”
Section: Introductionmentioning
confidence: 99%